2010
DOI: 10.1007/s00011-010-0182-8
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid combinations cause synergistic inhibition of proinflammatory mediator secretion from lipopolysaccharide-induced RAW 264.7 cells

Abstract: Some flavonoids are synergistic in their anti-inflammatory effects when combined. In particular chrysin and kaempferol significantly synergised in their inhibitory effect upon NO, PGE(2) and TNF-alpha secretion. These findings open further avenues of research into combinatorial therapeutics of inflammatory-related diseases and the pharmacology of flavonoid synergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 31 publications
3
40
0
Order By: Relevance
“…Here we reported that kaempferol attenuates DC activation for the first time. The similar inhibition of inflammatory cytokines (TNF-␣, IL-12, and IL-1␤) by kaempferol is also observed in LPS-stimulated macrophages (Fang et al 2005;Harasstani et al 2010;Kowalski et al 2005). This novel function may enhance the potential of kaempferol in medical applications, such as treatment of airway inflammation .…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Here we reported that kaempferol attenuates DC activation for the first time. The similar inhibition of inflammatory cytokines (TNF-␣, IL-12, and IL-1␤) by kaempferol is also observed in LPS-stimulated macrophages (Fang et al 2005;Harasstani et al 2010;Kowalski et al 2005). This novel function may enhance the potential of kaempferol in medical applications, such as treatment of airway inflammation .…”
Section: Discussionmentioning
confidence: 61%
“…Quercetin has recently been demonstrated to exhibit an immunosuppressive effect on DC activation (Huang et al 2010a). The presence of both kaempferol and quercetin may has synergistic effect (Harasstani et al 2010) and is probably the reason that the n-butanol extract of SC has stronger inhibitory activity than the methanol extract of SC, which mainly contains kaempferol alone (Fig. 1C).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Another reason for the beneficial effects of morin is the reported anti-inflammatory properties, which were demonstrated in earlier in vitro and in vivo studies [45,47] . Recently Chen et al reported that the morin treatments suppress the production of several pro-inflammatory biomarkers expressions such as NO, PGE-2, iNOS and COX-2 [48].…”
Section: Discussionmentioning
confidence: 97%
“…3,4 During an inflammatory process, activated macrophages initiate a diverse series of functional responses such as the production of nitric oxide (NO) and cytokines (eg, tumor necrosis factor [TNF], interleukin [IL], and growth factors) as well as the activation of phospholipase A 2 , which produces lipid metabolites of arachidonic acid (eg, prostaglandin [PG] and leukotrienes). [5][6][7] Recognition of bacterial LPS endotoxin and subsequent intracellular signal transduction cascades in macrophages are key in eliminating invading pathogens and deleterious stimuli. 8,9 Nevertheless, an excessive or continuous production of inflammatory mediators has been linked to the development of various acute and chronic human diseases, including septic shock, hemorrhagic shock, atherosclerosis, rheumatoid arthritis, ulcerative colitis, multiple sclerosis, hepatitis, pulmonary fibrosis, and cancer.…”
Section: Introductionmentioning
confidence: 99%